Glucose intolerance but normal satiety in mice with a null mutation in the glucagon–like peptide 1 receptor gene - Scrocchi, L.A.; Brown, T.J.; Maclusky, N.; Brubaker, P.L.; Auerbach, A.B.; Joyner, A.L.; Drucker, D.J. (Nature medicine, 1996)
Glucagon–like peptide 1 (GLP1) is postulated to regulate blood glucose and satiety, but the biological importance of GLP1 as an incretin and neuropeptide remains controversial. The regulation of nutrient–induced insulin secretion is dependent on the secretion of incretins, gut–derived peptides that potentiate insulin secretion from the pancreatic islets 1 . To ascertain the relative physiological importance of GLP1 as a regulator of feeding behavior and insulin secretion, we have generated mice with a targeted disruption of the GLP1 receptor gene ( GLP1R ). These GLP1R −/− mice are viable, develop normally but exhibit increased levels of blood glucose following oral glucose challenge in association with diminished levels of circulating insulin. It is surprising that they also exhibit abnormal levels of blood glucose following intraperitoneal glucose challenge. Intracerebroventricular administration of GLP1 inhibited feeding in wild–type mice but not in GLP1R −/− mice; however, no evidence for abnormal body weight or feeding behavior was observed in GLP1R −/− mice. These observations demonstrate that GLP1 plays a central role in the regulation of glycemia; however, disruption of GLP1/GLP1R signaling in the central nervous system is not associated with perturbation of feeding behavior or obesity in vivo .